Cellulose nanofiber composite phase change aerogel as well as preparation method and application thereof

By introducing inorganic nanoparticles and PEG materials into cellulose aerogels, the radiation cooling performance and energy storage temperature adjustment ability of cellulose nanofiber composite phase change aerogels are improved, and the problems of poor daytime cooling effect and nighttime supercooling are solved, and efficient radiation cooling and energy storage temperature adjustment are achieved.

CN119752420APending Publication Date: 2025-04-04SHAANXI UNIV OF SCI & TECH
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411823316.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing cellulose aerogels have poor radiation cooling effect in high temperature environments during the day, and may lead to supercooling at night or in low temperature environments, affecting indoor thermal comfort.

Method used

Cellulose nanofiber composite phase change aerogel is used to enhance its reflectivity and radiation cooling performance in the solar illuminated region by introducing inorganic nanoparticles TiO2-NH2 and PTW-NH2, and to use PEG's solid-liquid phase change material to store latent heat and adjust the temperature.

Benefits of technology

It achieves a more efficient radiation cooling effect in high-temperature environments during the day, with the average temperature reduced by 10.93℃, and prevents overcooling at night or in low-temperature environments, maintaining the comfort of indoor temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752420A_ABST
    Figure CN119752420A_ABST
Patent Text Reader

Abstract

The invention discloses cellulose nanofiber composite phase change aerogel as well as a preparation method and application thereof, and the method comprises the following steps: step 1, mixing 50-450 parts by mass of a polyvinyl alcohol solution with the concentration of 0.01-0.2 g / mL and 200-900 parts by mass of a cellulose nanofiber solution with the concentration of 1 wt%, and uniformly stirring to obtain a solution A; adjusting the pH value of the solution A to be acidic by using an acid solution, then adding 5-55 parts of a silane coupling agent I into the solution A, and uniformly stirring to obtain a solution B; then mixing TiO2-NH2 and PTW-NH2 according to a mass ratio of 1: 1 to obtain TiO2-NH2 / PTW-NH2, adding 1-10 parts of TiO2-NH2 / PTW-NH2 and 20-50 parts of PEG (Polyethylene Glycol) into the solution B, and uniformly stirring to obtain a mixed solution C; 2, the mixed solution C is injected into a mold and frozen, then freeze drying is conducted, and the cellulose nanofiber composite phase change aerogel is obtained, efficient radiation cooling and energy storage temperature adjusting performance is achieved, and the phenomenon of supercooling at night can be effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, and in particular is a cellulose nanofiber composite phase change aerogel and a preparation method and application thereof. Background Art

[0002] As the global climate warms, people's demand for refrigeration has increased significantly. Traditional cooling technologies, such as fans and air-conditioning systems, usually lead to large amounts of energy consumption and unnecessary greenhouse gas emissions, thereby exacerbating global warming. Therefore, it is crucial to develop energy-free and environmentally friendly cooling technologies.

[0003] Radiative cooling is the most promising refrigeration method. It cools objects spontaneously by radiating heat to the cold outer space (~3K) without any energy consumption or greenhouse gas emissions. The ideal radiative cooling material should show high emissivity in the full-wavelength solar spectrum and the infrared atmospheric window. Since cellulose aerogel contains a large number of CO and C-OH groups, it has high emissivity in the mid-infrared atmospheric transparent window. In addition, cellulose aerogel has an adjustable hierarchical porous structure, is lightweight and white, and has high reflectivity in the solar spectrum. Therefore, cellulose aerogel is a pollution-free, naturally degradable, green and environmentally friendly material that meets the conditions for radiative cooling. However, there are still two problems with existing cellulose aerogels: First, under direct sunlight, the average temperature can only be reduced by about 7°C compared with the daytime ambient temperature. When the temperature is high during the day or in summer, its radiative cooling effect still needs to be improved; Second, due to its inherent emissivity, it will continue to emit thermal radiation at night or in winter when the temperature is low, resulting in overcooling, which is not conducive to temperature regulation and leads to poor indoor thermal comfort. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a cellulose nanofiber composite phase change aerogel and a preparation method and application thereof, which realizes efficient radiation cooling and energy storage temperature regulation, and can effectively prevent overcooling at night.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a cellulose nanofiber composite phase change aerogel comprises the following steps:

[0007] Step 1, by mass: first, 50 to 450 parts of a polyvinyl alcohol solution with a concentration of 0.01 to 0.2 g / mL and 200 to 900 parts of a cellulose nanofiber solution with a concentration of 1 wt% are mixed and stirred to obtain a solution A; then, the pH value of the solution A is adjusted to acidic with an acid solution, and then 5 to 55 parts of a silane coupling agent I are added to the solution A and stirred to obtain a solution B; then, TiO 2 -NH 2 and PTW-NH 2 Mix according to the mass ratio of 1:1 to obtain TiO 2 -NH 2 / PTW-NH 2 , add 1 to 10 parts of TiO 2 -NH 2 / PTW-NH 2 and 20 to 50 parts of PEG, and stirred evenly to obtain a mixed solution C;

[0008] Step 2: Inject the mixed solution C into a mold and freeze it, followed by freeze drying to obtain a cellulose nanofiber composite phase change aerogel.

[0009] Furthermore, the silane coupling agent I in step 1 is KH560.

[0010] Furthermore, the acid solution in step 1 is an acetic acid solution, a hydrochloric acid solution or a sulfuric acid solution with a concentration of 0.5 mol / L.

[0011] Furthermore, the pH value of step 1 is 1-6.

[0012] Furthermore, the TiO 2 -NH 2 Prepared by the following method:

[0013] Step 1.1.1, according to the volume ratio (3-15): 1, take anhydrous ethanol and water and mix them evenly to obtain an ethanol solution;

[0014] Step 1.1.2: Add 5-55 parts of TiO2 into a three-necked flask containing 150-1000 parts of ethanol solution according to the mass fraction. 2 , ultrasonically dispersed uniformly to obtain solution D, and then 1-20 parts of silane coupling agent II were dropped into solution D, refluxed at 80°C for 12 hours, cooled to room temperature, filtered and washed with anhydrous ethanol and deionized water for 3-6 times, and vacuum dried at 80°C for 24 hours to obtain TiO 2 -NH 2 .

[0015] Further, the PTW-NH in step 1 2 Prepared by the following method:

[0016] Step 1.2.1, according to the volume ratio (3-15): 1, take anhydrous ethanol and water and mix them evenly to obtain an ethanol solution;

[0017] Step 1.2.2, according to the mass fraction, add 5-55 parts of PTW to a three-necked flask containing 150-1000 parts of ethanol solution, and disperse it uniformly by ultrasonication to obtain solution E, and then drop 1-20 parts of silane coupling agent II into solution E, reflux at 80°C for 12 hours, cool to room temperature, filter and wash with anhydrous ethanol and deionized water for 3-6 times, and vacuum dry at 80°C for 24 hours to obtain PTW-NH 2 .

[0018] Furthermore, the silane coupling agent II is KH550.

[0019] Furthermore, in step 1, the molecular weight of PEG is 1000, 2000, 4000, 6000 or 8000.

[0020] A cellulose nanofiber composite phase change aerogel.

[0021] Application of cellulose nanofiber composite phase change aerogel in the field of thermal management.

[0022] Compared with the prior art, the present invention has the following technical effects:

[0023] On the one hand, by introducing inorganic nanoparticles TiO 2 -NH 2 and PTW-NH 2 By utilizing the synergistic effect of the two, the reflectivity of the cellulose aerogel in the sunlight area is improved, and the radiation cooling performance of the cellulose aerogel in the daytime or other high-temperature environments is enhanced. Under direct sunlight, the average temperature is reduced by 10.93°C compared with the daytime ambient temperature; on the other hand, the solid-liquid phase change material PEG absorbs and releases a large amount of latent heat, so that the temperature of the cellulose aerogel at night is always higher than the ambient temperature, which effectively prevents the cellulose aerogel from being overcooled at night or in other low-temperature environments; therefore, the cellulose nanofiber composite phase change aerogel prepared by the present invention not only has good radiation cooling performance, but also has excellent energy storage and temperature regulation performance, which can effectively prevent the phenomenon of overcooling at night, and can be applied to the field of thermal management to achieve efficient radiation cooling and energy storage and temperature regulation.

[0024] The present invention adopts a method of first freezing and then freeze-drying. Ice crystals are fully formed in advance by freezing. During the freeze-drying process, the ice crystals sublime, which is conducive to forming a porous structure, helps to reflect sunlight, and further enhances the radiation cooling performance of the aerogel. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 : Change curves of the real-time temperature and ambient temperature during the day of the cellulose nanofiber composite phase change aerogel prepared in Example 2 of the present invention and the cellulose nanofiber composite phase change aerogel prepared in Comparative Example 1;

[0026] Figure 2 : A bar graph showing the temperature difference between the cellulose nanofiber composite phase change aerogel prepared in Example 2 of the present invention and the cellulose nanofiber composite phase change aerogel prepared in Comparative Example 1 and the daytime ambient temperature;

[0027] Figure 3 : Change curves of real-time temperature and ambient temperature at night for the cellulose nanofiber composite phase change aerogel prepared in Example 2 of the present invention and the cellulose nanofiber composite phase change aerogel prepared in Comparative Example 1. DETAILED DESCRIPTION

[0028] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0029] Example 1

[0030] Step 1: Preparation of TiO 2 -NH 2 and PTW-NH 2

[0031] Step 1.1, mix anhydrous ethanol and water in a volume ratio of 3:1 to obtain an ethanol solution;

[0032] Step 1.2: Add 5 parts of TiO 2 , ultrasonically dispersed uniformly to obtain solution D, and then 1 part of KH550 was dropped into solution D, refluxed at 80°C for 12 hours, cooled to room temperature, filtered and washed with anhydrous ethanol and deionized water three times, and vacuum dried at 80°C for 24 hours to obtain TiO 2 -NH 2 ;

[0033] Step 1.3, according to the mass fraction, add 5 parts of PTW to a three-necked flask containing 150 parts of ethanol solution, and disperse it evenly by ultrasonication to obtain solution E, then drop 1 part of KH550 into solution E, reflux at 80°C for 12 hours, cool to room temperature, filter and wash with anhydrous ethanol and deionized water three times, and vacuum dry at 80°C for 24 hours to obtain PTW-NH 2 ;

[0034] Step 2: Preparation of cellulose nanofiber composite phase change aerogel

[0035] Step 2.1, by mass: first, 50 parts of a polyvinyl alcohol (PVA) solution with a concentration of 0.01 g / mL and 200 parts of a cellulose nanofiber (CNF) solution with a concentration of 1 wt% were mixed, and stirred at a rate of 300 r / min for 4 h to obtain solution A; then, the pH value of solution A was adjusted to 1 with a 0.5 mol / L acetic acid solution, and then 5 parts of KH560 were added to solution A, and stirred at a rate of 300 r / min for 4 h to obtain solution B; then, TiO 2 -NH 2 and PTW-NH 2 Mix according to the mass ratio of 1:1 to obtain TiO 2 -NH 2 / PTW-NH 2 , add 3 parts of TiO 2 -NH 2 / PTW-NH 2 and 20 parts of PEG with a molecular weight of 1000, stirred at a rate of 300 r / min for 4 h to obtain a mixed solution C;

[0036] Step 2.2, injecting the mixed solution C into a mold and freezing it, followed by freeze drying, to obtain a cellulose nanofiber composite phase change aerogel.

[0037] Example 2

[0038] Step 1: Preparation of TiO 2 -NH 2 and PTW-NH 2

[0039] Step 1.1, mix anhydrous ethanol and water in a volume ratio of 9:1 to obtain an ethanol solution;

[0040] Step 1.2: Add 15 parts of TiO 2 , ultrasonically dispersed uniformly to obtain solution D, then 3 parts of KH550 were dropped into solution D, refluxed at 80°C for 12 hours, cooled to room temperature, filtered and washed with anhydrous ethanol and deionized water for 4 times, and vacuum dried at 80°C for 24 hours to obtain TiO 2 -NH 2 ;

[0041] Step 1.3: Add 15 parts of PTW to a three-necked flask containing 450 parts of ethanol solution by weight, disperse uniformly by ultrasonication to obtain solution E, then drop 3 parts of KH550 into solution E, reflux at 80°C for 12 hours, cool to room temperature, filter and wash with anhydrous ethanol and deionized water four times, and vacuum dry at 80°C for 24 hours to obtain PTW-NH 2 ;

[0042] Step 2: Preparation of cellulose nanofiber composite phase change aerogel

[0043] Step 2.1, by mass: first, 110 parts of a polyvinyl alcohol (PVA) solution with a concentration of 0.1 g / mL and 750 parts of a cellulose nanofiber (CNF) solution with a concentration of 1 wt% were mixed, and stirred at a rate of 400 r / min for 4 h to obtain solution A; then, the pH value of solution A was adjusted to 4 with a 0.5 mol / L acetic acid solution, and then 15 parts of KH560 were added to solution A, and stirred at a rate of 400 r / min for 4 h to obtain solution B; then, TiO 2 -NH 2 and PTW-NH 2 Mix according to the mass ratio of 1:1 to obtain TiO 2 -NH 2 / PTW-NH 2 , add 1 part of TiO 2 -NH 2 / PTW-NH 2 and 23 parts of PEG with a molecular weight of 2000, stirred at a rate of 400 r / min for 4 h to obtain a mixed solution C;

[0044] Step 2.2, injecting the mixed solution C into a mold and freezing it, followed by freeze drying, to obtain a cellulose nanofiber composite phase change aerogel.

[0045] Example 3

[0046] Step 1: Preparation of TiO 2 -NH 2 and PTW-NH 2

[0047] Step 1.1, mix anhydrous ethanol and water in a volume ratio of 12:1 to obtain an ethanol solution;

[0048] Step 1.2: Add 30 parts of TiO 2 , ultrasonically dispersed uniformly to obtain solution D, and then 10 parts of KH550 were dropped into solution D, refluxed at 80°C for 12 hours, cooled to room temperature, filtered and washed with anhydrous ethanol and deionized water for 5 times, and vacuum dried at 80°C for 24 hours to obtain TiO 2 -NH 2 ;

[0049] Step 1.3, according to the mass fraction, add 30 parts of PTW to a three-necked flask containing 750 parts of ethanol solution, and disperse it evenly by ultrasonication to obtain solution E, then drop 10 parts of KH550 into solution E, reflux at 80°C for 12 hours, cool to room temperature, filter and wash with anhydrous ethanol and deionized water successively for 5 times, and vacuum dry at 80°C for 24 hours to obtain PTW-NH 2 ;

[0050] Step 2: Preparation of cellulose nanofiber composite phase change aerogel

[0051] Step 2.1, by mass: first, 250 parts of a polyvinyl alcohol (PVA) solution with a concentration of 0.15 g / mL and 550 parts of a cellulose nanofiber (CNF) solution with a concentration of 1 wt% were mixed, and stirred at a rate of 500 r / min for 4 h to obtain solution A; then, the pH value of solution A was adjusted to 5 with a 0.5 mol / L hydrochloric acid solution, and then 30 parts of KH560 were added to solution A, and stirred at a rate of 500 r / min for 4 h to obtain solution B; then, TiO 2 -NH 2 and PTW-NH 2 Mix according to the mass ratio of 1:1 to obtain TiO 2 -NH 2 / PTW-NH 2 , add 5 parts of TiO 2 -NH 2 / PTW-NH 2 and 40 parts of PEG with a molecular weight of 4000, stirred at a rate of 500 r / min for 4 h to obtain a mixed solution C;

[0052] Step 2.2, injecting the mixed solution C into a mold and freezing it, followed by freeze drying, to obtain a cellulose nanofiber composite phase change aerogel.

[0053] Example 4

[0054] Step 1: Preparation of TiO 2 -NH 2 and PTW-NH 2

[0055] Step 1.1, mix anhydrous ethanol and water in a volume ratio of 15:1 to obtain an ethanol solution;

[0056] Step 1.2: Add 55 parts of TiO 2, ultrasonically dispersed uniformly to obtain solution D, then 20 parts of KH550 were dropped into solution D, refluxed at 80°C for 12 hours, cooled to room temperature, filtered and washed with anhydrous ethanol and deionized water for 6 times, and vacuum dried at 80°C for 24 hours to obtain TiO 2 -NH 2 ;

[0057] Step 1.3, according to the mass fraction, add 55 parts of PTW to a three-necked flask containing 1000 parts of ethanol solution, and disperse it evenly by ultrasonication to obtain solution E, then drop 20 parts of KH550 into solution E, reflux at 80°C for 12 hours, cool to room temperature, filter and wash with anhydrous ethanol and deionized water for 6 times, and vacuum dry at 80°C for 24 hours to obtain PTW-NH 2 ;

[0058] Step 2: Preparation of cellulose nanofiber composite phase change aerogel

[0059] Step 2.1, by mass: first, 450 parts of a polyvinyl alcohol (PVA) solution with a concentration of 0.2 g / mL and 900 parts of a cellulose nanofiber (CNF) solution with a concentration of 1 wt% were mixed, and stirred at a rate of 700 r / min for 4 h to obtain solution A; then, the pH value of solution A was adjusted to 6 with a 0.5 mol / L sulfuric acid solution, and then 55 parts of KH560 were added to solution A, and stirred at a rate of 700 r / min for 4 h to obtain solution B; then, TiO 2 -NH 2 and PTW-NH 2 Mix according to the mass ratio of 1:1 to obtain TiO 2 -NH 2 / PTW-NH 2 , add 10 parts of TiO 2 -NH 2 / PTW-NH 2 and 50 parts of PEG with a molecular weight of 6000, stirred at a rate of 600 r / min for 4 h to obtain a mixed solution C;

[0060] Step 2.2, injecting the mixed solution C into a mold and freezing it, followed by freeze drying, to obtain a cellulose nanofiber composite phase change aerogel.

[0061] Example 5

[0062] Step 1: Preparation of TiO 2 -NH 2 and PTW-NH 2

[0063] Step 1.1, mix anhydrous ethanol and water in a volume ratio of 6:1 to obtain an ethanol solution;

[0064] Step 1.2: Add 40 parts of TiO 2 , ultrasonically dispersed uniformly to obtain solution D, and then 15 parts of KH550 were dropped into solution D, refluxed at 80°C for 12 hours, cooled to room temperature, filtered and washed with anhydrous ethanol and deionized water three times, and vacuum dried at 80°C for 24 hours to obtain TiO 2 -NH 2 ;

[0065] Step 1.3, according to the mass fraction, add 40 parts of PTW to a three-necked flask containing 575 parts of ethanol solution, and disperse it evenly by ultrasonication to obtain solution E, then drop 15 parts of KH550 into solution E, reflux at 80°C for 12 hours, cool to room temperature, filter and wash with anhydrous ethanol and deionized water three times, and vacuum dry at 80°C for 24 hours to obtain PTW-NH 2 ;

[0066] Step 2: Preparation of cellulose nanofiber composite phase change aerogel

[0067] Step 2.1, by mass: first, 350 parts of a polyvinyl alcohol (PVA) solution with a concentration of 0.05 g / mL and 400 parts of a cellulose nanofiber (CNF) solution with a concentration of 1 wt% were mixed, and stirred at a rate of 600 r / min for 4 h to obtain solution A; then, the pH value of solution A was adjusted to 3 with a 0.5 mol / L hydrochloric acid solution, and then 40 parts of KH560 were added to solution A, and stirred at a rate of 600 r / min for 4 h to obtain solution B; then, TiO 2 -NH 2 and PTW-NH 2 Mix according to the mass ratio of 1:1 to obtain TiO 2 -NH 2 / PTW-NH 2 , add 8 parts of TiO 2 -NH 2 / PTW-NH 2 and 35 parts of PEG with a molecular weight of 8000, stirred at a rate of 600 r / min for 4 h to obtain a mixed solution C;

[0068] Step 2.2, injecting the mixed solution C into a mold and freezing it, followed by freeze drying, to obtain a cellulose nanofiber composite phase change aerogel.

[0069] Comparative Example 1

[0070] Step 1, by mass: first, 110 parts of a polyvinyl alcohol (PVA) solution with a concentration of 0.1 g / mL and 750 parts of a cellulose nanofiber (CNF) solution with a concentration of 1 wt% were mixed, and stirred at a rate of 400 r / min for 4 hours to obtain a solution A; then, the pH value of the solution A was adjusted to 4 with a 0.5 mol / L acetic acid solution, and then 15 parts of KH560 were added to the solution A, and stirred at a rate of 400 r / min for 4 hours to obtain a solution B; then, 23 parts of a PEG with a molecular weight of 2000 were added to the solution B, and stirred at a rate of 400 r / min for 4 hours to obtain a mixed solution C;

[0071] Step 2: Inject the mixed solution C into a mold and freeze it, followed by freeze drying to obtain a cellulose nanofiber composite phase change aerogel.

[0072] See also Figure 1 The daytime temperatures of the cellulose nanofiber composite phase change aerogel prepared in Example 2 and the cellulose nanofiber composite phase change aerogel prepared in Comparative Example 1 are both lower than the ambient temperature. In particular, the temperature of the cellulose nanofiber composite phase change aerogel prepared in Example 2 is lower than that of the cellulose nanofiber composite phase change aerogel prepared in Comparative Example 1, indicating that the introduction of inorganic nanoparticles TiO 2 -NH 2 and PTW-NH 2 , which can further improve the radiation cooling performance of cellulose nanofiber composite phase change aerogel.

[0073] See also Figure 2 The average temperature of the cellulose nanofiber composite phase change aerogel prepared in Example 2 under direct sunlight was reduced by 10.93°C compared with the daytime ambient temperature. Under the same conditions, the average temperature of the cellulose nanofiber composite phase change aerogel prepared in Comparative Example 1 was only reduced by 7.17°C compared with the daytime ambient temperature, indicating that the inorganic nanoparticles TiO 2 -NH 2 and PTW-NH 2 It can give cellulose nanofiber composite phase change aerogel more excellent radiation cooling performance.

[0074] See also Figure 3The temperature of the cellulose nanofiber composite phase change aerogel prepared in Example 2 and the cellulose nanofiber composite phase change aerogel prepared in Comparative Example 1 at night is higher than the ambient temperature, indicating that the latent heat stored in the solid-liquid phase change material PEG is gradually released, which effectively prevents the occurrence of nighttime supercooling. The temperature of the cellulose nanofiber composite phase change aerogel prepared in Example 2 is slightly higher than that of the cellulose nanofiber composite phase change aerogel prepared in Comparative Example 1. This is because, even at night, the cooling radiation performance of the cellulose nanofiber composite phase change aerogel prepared in Example 2 is better than that of the cellulose nanofiber composite phase change aerogel prepared in Comparative Example 1. However, the temperature difference between the two is not very large, indicating that the introduced inorganic nanoparticles TiO 2 -NH 2 and PTW-NH 2 The effect on the performance of cellulose nanofiber composite phase change aerogel in absorbing and releasing a large amount of latent heat is very small. Therefore, the cellulose nanofiber composite phase change aerogel prepared in Example 2 not only has good radiation cooling performance, but also has excellent energy storage and temperature regulation performance, which can effectively prevent overcooling at night.

Claims

1. A method for preparing a cellulose nanofiber composite phase change aerogel, characterized in that: The steps include: Step 1, by mass: first, 50 to 450 parts of a polyvinyl alcohol solution with a concentration of 0.01 to 0.2 g / mL and 200 to 900 parts of a cellulose nanofiber solution with a concentration of 1 wt% are mixed, and stirred evenly to obtain a solution A; then, the pH value of the solution A is adjusted to acidic with an acid solution, and then 5 to 55 parts of a silane coupling agent I are added to the solution A, and stirred evenly to obtain a solution B; then, TiO2-NH2 and PTW-NH2 are mixed in a mass ratio of 1:1 to obtain TiO2-NH2 / PTW-NH2, and 1 to 10 parts of TiO2-NH2 / PTW-NH2 and 20 to 50 parts of PEG are added to the solution B, and stirred evenly to obtain a mixed solution C; Step 2: Inject the mixed solution C into a mold and freeze it, followed by freeze drying to obtain a cellulose nanofiber composite phase change aerogel.

2. The method for preparing the cellulose nanofiber composite phase change aerogel according to claim 1, characterized in that: The silane coupling agent I in step 1 is KH560.

3. The method for preparing the cellulose nanofiber composite phase change aerogel according to claim 1, characterized in that: The acid solution in step 1 is acetic acid solution, hydrochloric acid solution or sulfuric acid solution with a concentration of 0.5 mol / L.

4. The method for preparing the cellulose nanofiber composite phase change aerogel according to claim 1, characterized in that: The pH value of step 1 is 1-6.

5. The method for preparing the cellulose nanofiber composite phase change aerogel according to claim 1, characterized in that: The TiO2-NH2 in step 1 is prepared by the following method: Step 1.1.1, according to the volume ratio (3-15): 1, take anhydrous ethanol and water and mix them evenly to obtain an ethanol solution; Step 1.1.2: Add 5 to 55 parts of TiO2 by mass into a three-necked flask containing 150 to 1000 parts of ethanol solution, disperse it evenly by ultrasonication to obtain solution D, then drop 1 to 20 parts of silane coupling agent II into solution D, reflux at 80°C for 12 hours, cool to room temperature, filter and wash with anhydrous ethanol and deionized water for 3 to 6 times, and vacuum dry at 80°C for 24 hours to obtain TiO2-NH2.

6. The method for preparing the cellulose nanofiber composite phase change aerogel according to claim 1, characterized in that: The PTW-NH2 in step 1 is prepared by the following method: Step 1.2.1, according to the volume ratio (3-15): 1, take anhydrous ethanol and water and mix them evenly to obtain an ethanol solution; Step 1.2.2, add 5 to 55 parts of PTW to a three-necked flask containing 150 to 1000 parts of ethanol solution according to mass parts, and disperse it evenly by ultrasonication to obtain solution E, then drop 1 to 20 parts of silane coupling agent II into solution E, reflux at 80°C for 12 hours, cool to room temperature, filter and wash with anhydrous ethanol and deionized water for 3 to 6 times, and vacuum dry at 80°C for 24 hours to obtain PTW-NH2.

7. The method for preparing the cellulose nanofiber composite phase change aerogel according to claim 5 or 6, characterized in that: The silane coupling agent II is KH550.

8. The method for preparing the cellulose nanofiber composite phase change aerogel according to claim 1, characterized in that: In step 1, the molecular weight of PEG is 1000, 2000, 4000, 6000 or 8000.

9. A cellulose nanofiber composite phase change aerogel prepared by the method according to any one of claims 1 to 8.

10. Use of the cellulose nanofiber composite phase change aerogel according to claim 9 in the field of thermal management.

Citation Information

Patent Citations

  • Method for preparing potassium hexatitanate whisker composite SiO2 aerogel heat insulating material

    CN101456720A

  • Multiple chemical crosslinking reinforced cellulose aerogel and preparation method thereof

    CN106349488A

  • Preparation method of polyvinyl alcohol / bagasse nano-cellulose aerogel

    CN108752623A

  • Light and heat storage type composite phase change material for energy storage and preparation method of light and heat storage type composite phase change material

    CN113136172A

  • Composite phase change material and preparation method thereof

    CN113174237A